Differential Signals From TNFα-Treated and Untreated Embryos in Uterine Tissues and Splenic CD4+ T Lymphocytes During Preimplantation Pregnancy in Mice - Buska-Mach, Katarzyna; Kedzierska, Anna Ewa; Lepczynski, Adam; Herosimczyk, Agnieszka; Ozgo, Małgorzata; Karpinski, Pawel; Gomulkiewicz, Agnieszka; Lorek, Daria; Slawek, Anna; Dziegiel, Piotr; Chelmonska-Soyta, Anna (Frontiers in Veterinary Science, 2021)
The main aim of this study was to examine if a female mouse body in preimplantation pregnancy can distinguish between embryos of normal and impaired biological quality in the local and peripheral compartments. Normal (Control group) and TNFα (tumor necrosis factor-α)-treated embryos (experimental group) at the morula stage were non-surgically transferred into the uteri f CD-1 strain (Crl:CD1(Icr)) female murine recipients. Twenty-four hours after the embryo transfer, females were euthanised, and uteri and spleens were dissected. In uterine tissues (local compartment), we assessed the expression of 84 genes comprising nine signal transduction pathways, using a modified RT² Profiler PCR Array. In the spleen (peripheral compartment), we determined the proteome of splenic CD4+ lymphocytes using 2D protein electrophoresis with subsequent protein identification by mass spectrometry. Sample clustering and differential gene expression analyses within individual signal transduction pathways revealed differential expression of genes in the uteri of females after transplantation of normal versus TNFα-treated embryos. The most affected signal transduction cascade was the NFKB (Nuclear factor NF-kappa-B) pathway, where 87.5% of the examined genes were significantly differentially expressed. Proteomic analysis of splenic CD4+ T lymphocytes revealed significant differential expression of 8 out of 132 protein spots. Identified proteins were classified as proteins influenced by cell stress, proteins engaged in the regulation of cytoskeleton stabilisation and cell motility, and proteins having immunomodulatory function. These results support the hypothesis that even before embryo implantation, the body of pregnant female mice can sense the biological quality of an embryo both at the local and peripheral level.